MUTU SOSIS FERMENTASI IKAN PATIN (Pangasius sp.) SELAMA PENYIMPANAN SUHU RUANG - Rita Marsuci Harmain; Linawati Hardjito; Winarti Zahiruddin (Department of Aquatic Product Technology IPB University in collaboration with Masyarakat Pengolahan Hasil Perikanan Indonesia (MPHPI), 2012)
Catfish (Pangasius sp.) is a potential commodity for local and export market. Fermented sausage wich is highly flavor product and has specific aroma provides health benefit. The study was aimed to characterise fermented sausage of catfish (Pangasius sp.) during storage at room temperature for 0, 4, 8, 12 and 16 days including hedonic sensory, microbiological and chemical characteristics. Fermented sausage of catfish using lactic acid bacteria Lactobacillus plantarum 1B1 used to optimize the fermentation process. Analysis conducted during storage include hedonic sensory (texture, color, flavor), chemical (pH and a) and microbiological (total plate count), total lactic acid bacteria L. plantarum 1B1, Escherichia coli, Staphylococcus sp., Salmonella sp., and mold/yeast) to obtain the best storage time. The result showed that the hedonic sensory was like-neutral, the chemical profile showed pH of 3,93-3,69 and aw of 0,88-0,79. Microbiological profile obtained total plate count 1.8 x108 CFU/g, total lactic acid bacteria L.plantarum 1B1 8.8 x 108 CFU/g. During storage there were no bacteria E. coli, Staphylococcus sp. and Salmonella sp., but the molds/yeasts obtained in storage on the 8th to 16th day.Key words: chemical, fermented sausage, hedonic sensory, microbiology, storage.